Chuck Berry : hail! Hail! Rock 'n' roll - Hackford, Taylor, 1945-; Berry, Ingrid; Clapton, Eric; Cray, Robert (Chatsworth, CA : Image Entertainment, 2006)
Profiles Chuck Berry's contribution to rock music through archival footage, interviews, and a concert celebrating his sixtieth birthday.
Originally released as a motion picture in 1988.
Features: introduction by Taylor Hackford, featurettes, bonus rehearsal footage, theatrical trailer.
Featuring Ingrid Berry, Eric Clapton, Robert Cray, Bo Diddley, Keith Richards.
DVDs, Dolby digital 5.1 surround.
Keywords: Berry, Chuck; African American rock musicians -- Biography; Rock musicians -- United States -- Biography; Rock music; Documentary films; Biographical films